The use of interactive methods in teaching professional speech to students - Mukaddas, Akhmedova; Nilufar, Dilmurodova (Linguistics and Culture Review, 2021)
Interactive teaching methods provide solutions to educational problems in various aspects. The use of interactive methods allows you to organize independent cognitive activity of students during the lesson. Possession of interactive learning technology and its use in the educational process will undoubtedly contribute to the development of students’ qualities that correspond to the processes taking place in life today. This paper presents the technologies of conducting Uzbek language lessons using interactive methods and their significance.